Environmental drivers of human migration in Sub-Saharan Africa - Sinafekesh Girma Wolde; Paolo D'Odorico; Maria Cristina Rulli (Global Sustainability)
Non-technical summary Environmental threats to shelter, livelihoods, and food security are often considered push factors for intra-African human migration. Research in this field is often fragmented into a myriad of case studies on specific subregions or events, thus preventing a more comprehensive understanding of the phenomenon. This paper examines environmental drivers reported in the literature as push factors for human displacement across 32 sub-Saharan African countries between 1990 and 2021. Extensive consultation of past studies and reports with analytical methods shows that environmental migration is complex and influenced by multiple direct and indirect factors. Non-environmental drivers compound the effects of environmental change.